The effect of breed and stage of lactation on the microbiological status of raw milk - Petróczki, Flóra Mária; Tonamo, Tema Andualem; Béri, Béla; Peles, Ferenc (Acta Agraria Debreceniensis, 2019)
The microbiological quality of the milk is important not only for food safety, but it can also influence the quality of dairy products. The microbiological status of raw cow milk can be influenced by many factors. Our aim was to determine whether there was a difference between the microbiological quality of milk of two different cow breeds (Holstein Friesian and Jersey) kept and milked in the same conditions, and how the microbiological quality of the raw cow milk changed during lactation (beginning, mid, and end). Samples were taken and analysed in July, August and September in 2018 from two dairy farms in Hajdú-Bihar county. During the conducted studies, the total plate count (TPC), the coliform count, the Staphylococcus aureus count and the coagulase-negative Staphylococcus (CNS) count of raw milk samples were determined. There was no significant difference (P>0.05) between the milk of the Holstein Friesian and Jersey breeds in the case of TPC. However, the mean coliform count of milk samples taken from Holstein Friesian cows was significantly lower (P<0.05) than the mean coliform count of milk samples taken from Jersey cows. S. aureus was detected in one of the twelve milk samples taken from Holstein Friesian cows, and in two of the eleven milk samples taken from Jersey cows. CNS was found in larger amount in milk samples taken from Holstein Friesian cows, and the difference was significant (P<0.05). Both TPC and CNS count were significantly higher (P<0.05) in individual milk samples taken at the end stage of lactation, than in samples taken in the earlier stages of lactation from Farm “A”. However, in the case of Farm “B”, there was no significant difference (P>0.05) in colony counts at different stages of lactation. S. aureus was only present in milk samples that collected from cows, which were at the beginning and middle stages of lactation. Testimg the hemolysin production ability of S. aureus strains isolated from the raw milk samples, only weak hemolysis was observed on blood agar. In case of antibiotic resistance testing, it was found that all strains were susceptible to cefoxitin, chloramphenicol, clindamycin, erythromycin, gentamicin, penicillin G, tetracycline and trimethoprim/sulphamethoxazole. Based on the results of our studies, staphylococci were detected in a higher amount in the milk of Holstein Friesian cows, and coliform bacteria were detected in a higher number in the milk of Jersey cows. Summing up the results of the milk samples taken from the different stages of lactation in one of the farms, it can be concluded that higher TPC and CNS count could be detected at the end stage of lactation than in the samples taken from the earlier stages of lactation. The fact that at the end of lactation the microorganisms could be detected in a higher colony count may be related to the fact that teats could be damaged during lactation by the milking machine, which increased the chance of imvading the microorganisms into the udder.